Ways to Reduce Power Losses in Mining Power Supply Lines - N. S. Antsiferov (Горные науки и технологии, 2019)
Electric energy is the most common and universal form of energy. It can be produced in large quantities near energy sources, transmitted to large distances, easily distributed between consumers and converted into mechanical, thermal, and light energy. Ensuring reliable and economical quality electric energy supply to mining enterprises with the optimal use of energy resources is one of the most important tasks facing the country's energy sector. In the Russian Federation, high degree of concentration of generating capacities at power plants has been achieved. The main capacities are concentrated in power plants with installed capacity of more than 1 million kW. High importance of the electric power industry is determined by the infrastructural nature of the industry and the direct relationship between the country's economic growth and the level of its development effectiveness. One of the most pressing problems of modern electricity supply is the problem of ensuring the quality of electric energy. The main reason for the deterioration in the electricity quality is widespread non-linear loads that create non-sinusoidal currents and voltage unbalance during their operation. The voltage unbalance is most often caused by the presence of an unbalanced load. Unbalanced load currents flowing through the elements of the power supply system cause unbalanced voltage losses in them. This results in appearance of unbalanced voltages on the terminals of electric apparatus. The voltage deviations at electric apparatus overdriven phase may exceed the normally acceptable values, while the voltage deviations at electric apparatus other phases may remain within the normal limits. In addition to the deterioration of the voltage mode at electric apparatus under the unbalanced voltage conditions, the operating conditions of both the electric apparatus and all the network elements are significantly worsened, and the reliability of the electrical equipment and the power supply system as a whole decreased. The paper considers the issues of reducing the voltage losses in power supply networks by improving quality of electric power.